Analyzing Higher Educational Students Approach towards Online Teaching Learning - DYPIMR, Mrs.Rupali Kalekar, (Design Engineering, 2021)
Now a day’s online teaching has turn into the new normal owing due to the Covid-19 pandemic. Growing advances of technology helped for online teaching as it is widely accepted as a feasible element in teaching and learning. Online mode of teaching and learning offers a great flexibility. Advances in information technology (IT) brought new challenges for traditional higher education to prepare faculties to teach online courses with technology. The present study sought to determine the attitudes of students towards online teaching. For the realization of main objective an online survey was distributed to the students from higher education through various social media platforms like Google form and Whatsapp.